Torn decisions, luck, and libertarian free will: comments on Balaguer's free will as an open scientific problem. - Kane, Robert (Philosophical Studies, 2014)
The author discusses aspects of free will as an open scientific problem highlighted in the book of philosopher Mark Balaguer. He mentions his agreement with Balaguer on the libertarian theory of free will along with the involvement of indeterminism in choices and process of deliberation. An overview of his comment on the centered event casual theory of colleague Randy Clarke is also presented.